RANCANG BANGUN GROUND STATION DENGAN TAMPILAN GRAPHICAL USER INTERFACE PADA WAHANA ROKET BERBASIS PROCESSING DAN MENGGUNAKAN ATMEGA 328 - I Nyoman Sumitra Tanaya; Ida Bagus Alit Swamardika; Duman Care Khrisne (Jurnal SPEKTRUM, 2021)
The design of the Ground Station with a Graphical User Interface display on a Processingbasedrocket vehicle and using the ATmega328 is designed to be able to assist in monitoringthe environment of the rocket vehicle on the Ground Station with a Graphical User Interfacedisplay. The monitored environmental conditions include the Altitude parameter (Meter abovesea level) which is detected using an Altimeter, Attitude Indicator (the position of the rocketwhich includes the value of the rotation angle of the Pitch, Roll, and Yaw), the position of thevehicle according to the longitude value and latitude detected by GPS (GeographicalPositioning System), pointer display on each latitude and longitude point value in theGeographic Information System, Heading Indicator and real-time log data. GS can display datausing an IC (Integrated Circuit) which has been integrated with an accelerometer, gyro, GPSsensors, and a communication module on a Microcontroller that can be placed on a rocketvehicle so that the IC can be called a rocket module. The rocket module is then connected tocommunicate with the GS using the 2.4 GHz XBee. The results of this research indicate that theGUI can display the Pitch and Roll value angles of 32.75o and 4.15o which are implemented withthe attitude indicator display movement, get a Yaw angle value of 132.23o, can display anAltimeter with a ride height of 79 meters above sea level, followed by real-time log data displayand GIS as a map display containing points for each change in latitude and longitude.